Essays on dimensions of free and fair elections : frameworks, integrity, transparency, attributes, monitoring - Dundas, Carl W. (Commonwealth Secretariat LondonGB, 1994)
Identifies the principal ingredients for free and fair elections viz. an acceptable legal framework; the safeguarding of election integrity; the need for transparency of action; the basic attributes of a free and fair election and the interest and role of election observers - both local and international.